2015
DOI: 10.1063/1.4917212
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of amorphous Fe93Zr7 films: Effect of light ion implantation

Abstract: The Curie temperature (Tc) of amorphous FeZr alloys can be greatly enhanced by doping with light elements. In this investigation, ion implantation is used to dope Fe93Zr7 thin films with H, He, B, C, and N. Extended X-ray absorption fine structure measurements confirm that the amorphous structure is preserved upon implantation for all samples, except for the N-implanted sample which is partially crystallized. The Curie temperature increases from 124 K for the pristine FeZr sample to about 400 K for the (FeZr)B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…A sample was deposited from a compound target and the details about the sample preparation are given in Ref. 32 . and samples were deposited via co-sputtering from individual Fe and Zr targets at room temperature on 3 Si (001) substrates.…”
Section: Methodsmentioning
confidence: 99%
“…A sample was deposited from a compound target and the details about the sample preparation are given in Ref. 32 . and samples were deposited via co-sputtering from individual Fe and Zr targets at room temperature on 3 Si (001) substrates.…”
Section: Methodsmentioning
confidence: 99%
“…Fe-Zr-B 𝑇 𝐶 series metallic glasses, however, are more promising candidates for the application of room temperature magnetic refrigeration due to their being relatively nearer to the 𝑇 𝐶 room temperature. The effect of elements doping on the magnetic properties of Febased amorphous alloys has been studied in literature [20,21] and they show that adjusting the compositions is a feasible method to obtain materials with desired properties. In this work, different new minor additions into FeZrB systems were attempted and the effect was investigated in order to further understand the relationship between MCE and its composition.…”
Section: Introductionmentioning
confidence: 99%
“…Zamani et al [38,39] and Moubah et al [40,41] studied the effect of light ion implantation (H, He, B, C, and N) on the Curie temperature of amorphous Fe 93 Zr 7 films, together with extended x-ray absorption fine structure (EXAFS) measurements. They observed that the increase of T C is proportional to the increase in the average Fe-Fe distance, which allowed them to conclude that the dominant cause of the T C enhancement of amorphous Fe 93 Zr 7 upon doping is a volume effect.…”
Section: Introductionmentioning
confidence: 99%